Pengaruh Lingkungan Kerja, Motivasi Kerja Dan Stres Kerja Terhadap Kinerja Pegawai - Prabowo, Lindu; Sanusi, Anwar; Sumarsono, Tanto (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2018)
The purpose of this study is To describe the variables Work Environment, Motivation, Job Stress and Employee Performance. The population in this study amounted to 56 people. To collect the data the researcher used questionnaires. For descriptive and regresion analysis SPSS version 20 were applied. Based on the result of research indicate that 1). Work environment does not significantly affect employee performance, because the work environment culture is well established 2). Motivation of work affect the performance of employees, the better the motivation the better the performance of employees, 3). Job stress affects the performance of employees, the more stress increases the more increases the performance of employees, 4). Motivation is a variable that has a dominant influence on employee performance, so the motivation must be considered well by the leader.